Observations on the exploitation of penaeid prawn resources in the Palk Bay off Mandapam during 1986 - '93 - Maheswarudu, G; Manickam, P E Sampson; Rao, P Vedavyasa; Arputharaj, M R (Indian Journal of Fisheries, 2011)
The penaeid prawns contributed to 16.70% of the total trawl landings atMandapam during 1986-'93. Out of the ten species represented in the catch,four species namely Penaeus semisulcatus, Metapenaeopsis stridulans,Trachypenaeus pescadoreensis and Metapenaeus burkenroadi supported thefishery throughout the year. Contributing to over 50%, P. semisulcatus wasthe dominant species, followed by M. stridulans. Over the years a gradualdecline of P.semisulcatus in the species percentage composition and a steadyincrease of that of M. stridulans was observed. The change in the speciescomposition during 1986-'93 has been discussed. May to August was the peakseason for the fishery. Two peak seasons, one during May-August and the otherduring November-December were observed for P. semisulcatus. The annualfishing effort fluctuated between 3,54,055 and 6,48,513 hours with an averageof 4,90,361 hours. The annual prawn catch ranged from 561 to 1,065.8 t, theaverage annual catch being 703.5 t. The annual catch per hour ranged from0.8 to 2 kg. The MSY and corresponding optimum fishing effort was 726.2 tand 5,61,415 hours respectively.